2023
DOI: 10.14309/ajg.0000000000002251
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Minimal Hepatic Encephalopathy in Patients With Liver Cirrhosis: A Multicenter Study

Abstract: INTRODUCTION:The prevalence of minimal hepatic encephalopathy (MHE), in particular in different subgroups, remains unknown. This study aimed to analyze the prevalence of MHE in different subgroups to identify patients at high risk and to pave the way for personalized screening approaches.METHODS:In this study, data of patients recruited at 10 centers across Europe and the United States were analyzed. Only patients without clinical signs of hepatic encephalopathy were included. MHE was detected using the Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…16,17,[19][20][21] However, either no further analysis was performed, or further investigation of risk factors for MHE in some studies subsequently ruled out the etiology. 20,21 On the contrary, studies have also shown that the prevalence of MHE in patients with alcoholic cirrhosis is significantly higher than that in patients with other causes of cirrhosis at the time of the preliminary analysis; moreover, as an independent influencing factor, there is a synergistic effect with cirrhosis, exacerbating cognitive impairment in affected patients. Although HCV infection is associated with cognitive impairment, no significant difference has been found in multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,17,[19][20][21] However, either no further analysis was performed, or further investigation of risk factors for MHE in some studies subsequently ruled out the etiology. 20,21 On the contrary, studies have also shown that the prevalence of MHE in patients with alcoholic cirrhosis is significantly higher than that in patients with other causes of cirrhosis at the time of the preliminary analysis; moreover, as an independent influencing factor, there is a synergistic effect with cirrhosis, exacerbating cognitive impairment in affected patients. Although HCV infection is associated with cognitive impairment, no significant difference has been found in multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…43 Previous studies have been fairly consistent in showing that age, years of education, and MELD-Na scores are risk factors for MHE, and the results of our preliminary analysis were in agreement with this. [20][21][22] In addition, because etiology was found to be an independent risk factor for the occurrence of MHE in our preliminary analysis, we considered it separately according to etiology. Except for studies that explicitly included patients with specific etiologies, few studies to date have explored risk factors separately according to etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is recommended that all patients with liver cirrhosis undergo regular screening for MHE, especially those who have a history of hepatic encephalopathy, driving is a part of their daily activities, or have undergone a liver transplant. Screening should also be considered in patients with advanced liver disease or those who are at high risk for developing MHE (40).…”
Section: Screening Of Minimal Hepatic Encephalopathymentioning
confidence: 99%